Epistemology of Khidmah in Islamic Marketing and the Impact on Consumer Satisfaction - Chairunnisa Chairunnisa; Annisah Budiwati (Universitas Ahmad Dahlan, 2025)
Introduction : The Concept of Khidmah in Sharia Marketing emphasizes the values of sincere service, honesty, and fairness while ensuring that products remain halal and beneficial. This approach fosters both material and spiritual consumer satisfaction while building long-term harmonious relationships. This article employs descriptive qualitative research methods with descriptive procedures and techniques, focusing on data sources from literature, particularly relevant references to the object of study. The findings of this study indicate that the concept of Khidmah in Islamic marketing plays a crucial role in establishing harmonious relationships between business practitioners and consumers. Sincere, responsive, and ethical services not only enhance consumer satisfaction and loyalty but also create blessings and long-term benefits, positioning Islamic marketing as a sustainable solution for business success and societal well-being. Purpose: This article aims to explore the concept of Khidmah in Islamic marketing and its impact on consumer satisfaction, emphasizing the values of sincere service, honesty, and fairness in business practices. Methodology: This research adopts a descriptive qualitative approach, with data collection sourced from literature and descriptive analysis to understand the relationship between the concept of Khidmah and consumer satisfaction. Findings: The findings of this study indicate that the application of the concept of Khidmah in Islamic marketing plays a significant role in building harmonious relationships between business practitioners and consumers. This not only enhances consumer satisfaction and loyalty but also creates blessings and long-term benefits for all parties involved.